ANALISIS MOTIVASI PEKERJA KONSTRUKSI PADA MASA PANDEMI COVID-19 DI JAKARTA - Samuel Yohanes Setiawan; Arianti Sutandi (JMTS: Jurnal Mitra Teknik Sipil, 2022)
The construction industry is one of the industries experiencing various obstacles due to the COVID-19 pandemic. The motivation of workers has a close relationship in the construction industry as one of the factors that affect the productivity of construction projects. Employee motivation is one of the keys to maintaining the productivity level of construction projects during the COVID-19 pandemic. In this study, we will discuss the motivation of construction workers during the COVID-19 pandemic. The method used in this research is to use a questionnaire and data analysis using SmartPLS 3.0. This study aims to determine the factors that influence the motivation of construction workers during the COVID-19 pandemic in Jakarta. The construction workers under review are located at various project sites in Jakarta. From the results of the study, the level of need that most influenced the motivation of workers during the pandemic was Social Needs, while the indicator of the variable that most influenced it was good work supervision. The results of the analysis show differences in the level of motivational needs of workers before and after the COVID-19 pandemic from Physiological Needs to Social Needs.   Abstrak Industri konstruksi merupakan salah satu industri yang mengalami berbagai hambatan akibat pandemi COVID-19. Faktor motivasi pekerja memiliki hubungan yang erat dalam industri konstruksi sebagai salah satu faktor yang mempengaruhi produktifitas dari pembangunan proyek konstruksi. Motivasi pekerja merupakan salah kunci dalam menjaga tingkat produktifitas proyek konstruksi di masa pandemi COVID-19. Dalam penelitian ini, peneliti akan membahas mengenai motivasi pekerja konstruksi pada masa pandemi COVID-19. Metode yang digunakan dalam penelitian ini adalah dengan menggunakan kuesioner dan metode analisis menggunakan SmartPLS 3.0. Penelitian ini bertujuan untuk mengetahui faktor yang mempengaruhi motivasi pekerja konstruksi di masa pandemi COVID-19 di Jakarta. Pekerja konstruksi yang di tinjau berada di berbagai lokasi proyek di Jakarta. Berdasarkan hasil penelitian, faktor yang paling mempengaruhi motivasi pekerja pada masa pandemi adalah Social Needs secara khusus pada indikator variabel pengawasan kerja yang baik. Hasil Analisis juga menunjukan perbedaan tingkat kebutuhan motivasi pekerja sebelum pandemi COVID-19 dan setelah pandemi COVID-19 dari Physiological Needs menjadi Social Needs.